2000
DOI: 10.1002/1097-4644(20001215)79:4<686::aid-jcb160>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2-vitamin D3 affects the subcellular distribution of protein kinase C isoenzymes in rat duodenum: Influence of aging

Abstract: We have previously shown that the steroid hormone 1, 25-dihydroxy-vitamin D(3) [1,25(OH)(2)D(3)] stimulates total cell protein kinase C (PKC) activity in rat duodenum, an effect that is severely impaired in old animals. We further examined the role of 1, 25(OH)(2)D(3) on PKC as it relates to aging by measuring hormone-induced changes in subcellular localization of PKC activity and isoenzymes in duodenal mucosae from young (three-month-old) and aged (24-month-old) rats. Short treatment of duodenum with 1, 25(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…These multiple roles suggest that this group of enzymes is involved in the regulation of the health and damage of epithelial cells and the intestinal barrier. Thus, it is not surprising that these enzymes are modified by a wide variety of physical and physiological stimuli such as age (Balogh et al, 2000), diet (Murray et al, 2002), and hormones (Balogh et al, 2000). Nevertheless, the de-tailed mechanisms by which PKC isoforms are involved in these vital pathways remains to be elucidated.…”
Section: Protein Kinasesmentioning
confidence: 99%
“…These multiple roles suggest that this group of enzymes is involved in the regulation of the health and damage of epithelial cells and the intestinal barrier. Thus, it is not surprising that these enzymes are modified by a wide variety of physical and physiological stimuli such as age (Balogh et al, 2000), diet (Murray et al, 2002), and hormones (Balogh et al, 2000). Nevertheless, the de-tailed mechanisms by which PKC isoforms are involved in these vital pathways remains to be elucidated.…”
Section: Protein Kinasesmentioning
confidence: 99%
“…PKC␤ and -␦ were not detected in duodenal mucosa in mice. The study of Balogh et al (1), however, showed that PKC␣, -␤, and -␦, but not PKC⑀ and -were expressed in rat duodenal mucosa. This discrepancy may be related to species or to methodological differences.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that PKC-δ is also expressed in the duodenum (6,7) and that activation of duodenal mucosal PKC-δ inhibits glucose production (6). Although duodenal PKC-δ activation (6) or CCK action (2) is necessary for lipid sensing and sufficient to trigger a gut–brain–liver axis to lower glucose production, the interfunctional relationship between PKC-δ and CCK has yet to be established.…”
mentioning
confidence: 99%